Communicative Approaches to Restoration Ecology : a case study from Dovre Mountain and Svalbard, Norway - Hagen, Dagmar; Aasetre, Jörund; Emmelin, Lars (Carfax, 2002)
Extensive damage to arctic and alpine landscapes raises the question of resoration as a management strategy. Social science and planning concepts and methods are needed to handle the value judgements in resoration. Restoration of two areas was investigated using qualitative and participatory methods. Four possible restoration scenarios were investigated.